2016
DOI: 10.1111/anae.13406
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled oral analgesia versus nurse-controlled parenteral analgesia after caesarean section: a randomised controlled trial

Abstract: SummaryWe assessed the effectiveness of early patient-controlled oral analgesia compared with parenteral analgesia in a randomised controlled non-inferiority trial of women undergoing elective caesarean section under regional anaesthesia. Seventy-seven women received multimodal paracetamol, ketoprofen and morphine analgesia. The woman having patient-controlled oral analgesia were administered four pillboxes on the postnatal ward containing tablets and instructions for self-medication, the first at 7 h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
4
1
2
Order By: Relevance
“…One study of postpartum pain management showed similar findings, where patients in the PCOA group used fewer analgesics than patients receiving standard care (East et al, 2007). Other studies of IV-PCA (McNicol et al, 2015) and PCOA (Bonnal et al, 2016) have shown an increase in the use of opioids postoperatively, which is the opposite finding to our study. The difference might be explained by the fact that fewer patients in the PCOA group underwent surgery than in the control group in our study.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
See 2 more Smart Citations
“…One study of postpartum pain management showed similar findings, where patients in the PCOA group used fewer analgesics than patients receiving standard care (East et al, 2007). Other studies of IV-PCA (McNicol et al, 2015) and PCOA (Bonnal et al, 2016) have shown an increase in the use of opioids postoperatively, which is the opposite finding to our study. The difference might be explained by the fact that fewer patients in the PCOA group underwent surgery than in the control group in our study.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…The pattern with a lower pain score in our study is equivalent to studies of IV-PCA (Birnbaum et al, 2012, McNicol et al, 2015; however, neither our study nor other studies on PCOA (Bonnal et al, 2016;East et al, 2007;Kastanias et al, 2010) have shown a significant decrease in pain scores as in the studies with IV-PCA (Birnbaum et al;2012, McNicol et al, 2015. An explanation of the differences could be the lack of instructions to the patients on how to use the PRN analgesics in PCOA.…”
Section: Accepted Manuscriptcontrasting
confidence: 54%
See 1 more Smart Citation
“…In accordance with the former study, we found that the multidrug therapy was more effective than the single drug therapy in postoperative pain relief. Bonnal A et al, compared multimodal analgesia and patient controlled oral analgesia in elective caesarean section and found that multimodal analgesia is advantageous than patient controlled analgesia in relieving pain but no differences were noted for other adverse events and maternal satisfaction 16 . Roman Schumann et al, in their study proposed that the multimodal therapy is more effective than the single modal therapy in postoperative pain management 17 .…”
Section: Discussionmentioning
confidence: 99%
“…14 There is evidence that oral opioid alternatives to IV-PCA have equivalent analgesic effects in the postoperative period with a lower incidence of adverse effects. [15][16][17] Patient-controlled oral analgesia (PCOA) is a novel method of oral opioid administration practiced at our institution whereby breakthrough pain is managed with a set dose of a short-acting oral opioid that is available at the patient's bedside and is replaced if exhausted following regular lockout intervals (every two hours) while patients record pain levels and opioid use. 18 Patient-controlled oral analgesia may offer benefits such as a better analgesic profile, increased mobility, and less constipation, 19 and allows patients to vary their analgesia more easily according to pain and activity levels, 20 while minimizing costs.…”
Section: Re ´Sumementioning
confidence: 99%